Tianqi Jiangtang Capsule in the treatment of patients with diabetes: a systematic review and meta-analysis - Liu, Yanjiao; Chen, Yifan; Wang, Liuding; Jiang, Zhonghui; Gao, Zhuye (Frontiers in Pharmacology, 2026)
BackgroundTianqi Jiangtang Capsule (TJC) is a commercial Chinese polyherbal preparation (CCPP) commonly used as adjunctive therapy for glucose management in diabetes. While its potential multi-system effects have been observed, a systematic evaluation focusing on glycemic control remains limited. This study aims to primarily assess the glucose-lowering efficacy of TJC in diabetic patients.Materials and MethodsWe conducted a comprehensive search for relevant randomized controlled trials (RCTs) across nine electronic databases from their inception to 1 September 2025. Two independent reviewers performed trial selection, data extraction, and risk-of-bias assessment. Meta-analyses of efficacy and safety outcomes were performed using RevMan 5.3 and Stata 17. Evidence quality was evaluated using GRADE methodology.Results13 RCTs involving 1,298 diabetic patients were included. Compared with conventional treatment (CT) alone or combined with placebo, TJC plus CT significantly improved primary glycemic parameters: glycated hemoglobin (mean difference [MD] = −1.22, 95% confidence interval [CI] −1.70 to −0.74, P < 0.01), fasting blood glucose (MD = −1.37, 95% CI -1.74 to −0.99, P < 0.01), and 2 h postprandial blood glucose (MD = −2.07, 95% CI -2.56 to −1.58, P < 0.01). As exploratory findings, TJC also demonstrated beneficial effects on lipid profiles, inflammatory markers, and renal function. No significant difference was observed in the incidence of adverse events between groups.ConclusionTJC significantly improves glycemic control in patients with diabetes and shows potential multi-system benefits. However, its efficacy and safety profile require further validation in large-scale, high-quality trials, particularly regarding the influence of genetic factors on treatment response.